Clinical and radiologic features in patients with the WHO grade I and II meningiomas (Journal of Health Sciences, 2024)
Introduction: Meningiomas are the most common benign tumor of the central nervous system, accounting for 53.3% and 37.6% of all central nervous system tumors (1). The World Health Organization (WHO) Grade I meningiomas account for 80.5% of all meningiomas and are considered benign meningiomas; the WHO Grade II meningiomas account for 17.7% of all meningiomas and exhibit more aggressive behavior.Methods: In the period 2015-2022, a retrospective single-center study at the clinic of neurosurgery at the Clinical Center University of Sarajevo was conducted, which included patients with a pathohistological finding of WHO Grade I or II meningioma. Depending on the pathohistological grade of the tumor, patients were divided into two groups: Grade I and Grade II patients. Patients were examined clinically and radiologically. Clinical data collected included in the study: Gender, age, number of symptoms before surgery, whether patients were symptomatic or asymptomatic, pre-operative Eastern Cooperative Oncology Group,and Karnopsky performance scale. Pre-operative contrast magnetic resonance imaging of the head measured tumor volume, temporal muscle thickness (TMT), sagittal midline shift, and surrounding cerebral edema.Results: A total of 80 patients were enrolled in the study, 68 with WHO Grade I and 12 with WHO Grade II meningiomas. We found that patients with Grade I meningioma were younger and that the mean thickness of the temporal muscle was statistically thicker than in patients with Grade II. Increasing TMT was significantly and positively associated with Grade I tumors and negatively associated with Grade II tumors (p = 0.032).Conclusion: This study demonstrates that TMT can serve as a radiologic pre-operative indicator of meningioma grade and provide valuable guidance to neurosurgeons in surgical planning. Further studies are needed to validate these results.